Tak zwana ceramika husycka z Nowej Wsi, stan. 6, gm. Włocławek, woj. kujawsko-pomorskie - Pochylski, Mariusz; Kowalczyk, Andrzej (Acta Universitatis Lodziensis. Folia Archaeologica, 2011)
In the course of archaeological rescue works before the A1 motorway building in 2008 in Nowa Wieś site 6, Włocławek commune, relics of a late medieval and modern manorial farm and a late medieval manor house were recognized. The most numerous group of artifacts included crushed pottery from among which 12 fragments of so-called Hussite pottery have been distinguished (table I, II). The fragments come from at least 6 containers, including 5 wheel-made ones, made of clay with an admixture of fine-grained sand and one fragment from strongly lathed vessel made of identical ceramic mass as the wheel-made vessels. The containers in the passage between the belly and the short, weakly accentuated necks were decorated with horizontal bands of impressed with the use of a knurl letters. The preserved edge parts of most probably 4 pots have similarly shaped rims (table I: 1, 3, 4, 6, 8, II: 1–4,9). During the ring in reducing atmosphere all the fragments became grey (RAL 7033) to dark grey (RAL 7012) on their inner and outer surfaces. The fractures were 0.3–0.5 cm thick, in 8 cases were one-coloured (fig. 2: 1), grey (RAL 7033) or darkgrey (RAL 7012), in other cases – two-coloured (fig. 2: 2) with grey-light brown centre (RAL 8001). On all the specimens not big chips in places of white grains of marl or gypsum occurrence were registered (fig. 3). No special dispersion of the artifacts has been stated at the site. Only 1 fragment was explored in a pit (object A219), in the filling containing materials of chronology defined as the 16th century. The other were registered in objects and cultural layer, which occurred in the late modern period, in fillings containing materials dated to the 15th to 18th centuries. A characteristic ornament of letters, letter-like signs and letters impressed with a rotary stamp in the described collection appears in 4 variants (fig. 4). In 2 cases a full turn of the knurl consists of a row of 5 letters (variants II and III; fig. 5: 1, 2), in one case – 6 signs (variant IV; fig. 5: 3). In the collection from Nowa Wieś most frequent capital letters are: S in a mirror image, G u-turned, M turned left or right at a right angle, B written properly and u-turned, and D impressed properly or u-turned. In the period of the spread of the Hussite ideas in Kuyavia certain sequences of capital letters registered on vessels conveyed definite content to the initiated people. With time, signs transferred by potters with the use of another knurls became only symbols of religious-social movements (in the 16th century), and later they were only kinds of decoration (cf. Kajzer 1988, 1994; Andrzejewska 1997). It should be emphasized that on one fragment in metopes some signs have been recognized, which accompanied an inscription "maria", registered on a late medieval vessel from Kozi Hrádek in Czech. What is also worth attention is a complicated geometrical ornament and a horizontal band formed by 10 wavy parallel lines identified on a bowl (table III: 1, 2), direct analogies to which are found on late medieval vessels decorated with inscriptions from Czech. Probably not only letters made with the use of a knurl should be treated as an ornament typical of so-called Hussite pottery.